Revealing a preference for mixtures: An experimental study of risk - Paul Feldman; John Rehbeck (Quantitative Economics, 2022)
Using a revealed preference approach, we conduct an experiment where subjects make choices from linear convex budgets in the domain of risk. We find that many individuals prefer mixtures of lotteries in ways that systematically rule out expected utility behavior. We explore the extent to which an individual's preference to choose mixtures is related to a preference for randomization by comparing choices from a convex choice task to the decisions made in a repeated discrete choice task. We find that a preference to mix is positively correlated with behavior from repeated discrete choice tasks. Risk preferences preference for randomization stochastic choice revealed preferences C91 D81 D91
Keywords: C91; D81; D91; 330; Risk preferences; preference for randomization; stochastic choice; revealed preferences